Determination of Biogenic Amines Using Image Analysis of Ninhydrin-Visualized Biogenic Amine Spots in Thin Layer Chromatography - Barcelo, Jonathan M.; Alvarado, Jaybee; Magisa, Patricia Denise; Opalec, Yanna Kathleen; Peralta, Hazelle; Ramos, Katherine; Saldua, Claudine (Silliman Journal, 2022)
Image analysis was performed on ninhydrin-visualized spots of putrescine dihydrochloride, cadaverine dihydrochloride, spermidine trihydrochloride and tyramine hydrochloride in thin layer chromatography using the ImageJ software. The original image was processed and analyzed to determine Rf values, pixel area, mean gray values and circularity. The TLC methodology produced adequate differential separation of tyramine hydrochloride and cadaverine dihydrochloride from putrescine dihydrochloride and spermidine trihydrochloride in biogenic amine mixtures and fish paste extract. Regression equations showed adequate linearity when the pixel areas (R2 > 0.946, ρ<0.01) and mean gray values (R2 > 0.866, ρ<0.01) were utilized. TLC-image analysis using ImageJ software shows good potential in quantifying biogenic amines in aqueous solutions and food samples due to its low cost and simplicity